Living labs : design and assessment of sustainable living - Keyson, David V.; Guerra Santin, Olivia; Lockton, Dan (Springer, 2017)
This book presents the results of a multi-annual project with sustainable Living Labs in the United Kingdom, Sweden, Germany and the Netherlands. Living Labs? as initiated by the authors? have proved to be very promising research, design, co-creation and communication facilities for the development and implementation of sustainable innovations in the home. The book provides an inspiring introduction to both the methodology and business modelling for the Living Lab facilities. Understanding daily living at home is key to designing products and services that support households in their transition to more sustainable lifestyles. This book not only explores new ways of gaining insights into daily practices, but also discusses developing and testing design methods to create sustainable solutions for households. These new methods and tools are needed because those available are either ineffective or cause rebound-effects. Intended for researchers and designers with an interest in the transition to sustainable lifestyles, it also appeals to company leaders interested in new ways of developing sustainable innovations and offers suggestions for effectively applying Living Labs for sustainable urban development.- Resumé vydavatel
Keywords: elektronické knihy; electronic books